The Influence of ChatGPT Integration, Team Collaboration, and Communication Patterns on Student Project Performance in Software Engineering Practicum at a Private University in West Java - Soelistianto, Farida Arinie; Triwiyatno, Aris; Karnoto, Karnoto (Westscience Press, 2025)
This study examines the effects of ChatGPT integration, team collaboration, and communication patterns on student project performance in a Software Engineering Practicum course at a private university in West Java, Indonesia. The emergence of generative AI tools such as ChatGPT presents new opportunities for enhancing learning engagement and teamwork in higher education. Using a quantitative approach, data were collected from 150 students through a Likert-scale questionnaire, and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS 3). The findings reveal that ChatGPT integration has a significant positive impact on both team collaboration and communication patterns, which in turn strongly influence project performance. Among all variables, communication patterns emerged as the strongest predictor of success, followed by team collaboration and ChatGPT integration. Furthermore, team collaboration mediates the relationship between ChatGPT use and project performance, indicating that AI tools are most effective when embedded within social learning processes. The model demonstrated high explanatory power (R² = 0.790) and strong predictive relevance (Q² = 0.785). These results highlight that ChatGPT acts not as a replacement for human effort, but as a cognitive collaborator that strengthens teamwork and communication, ultimately enhancing learning outcomes in AI-assisted project-based education.